Speech recognition technology applications in communication disorders. - Venkatagiri HS (American Journal of Speech-Language Pathology, 2002)
Speech recognition (SR) is the process whereby a microprocessor-based system, typically a computer with sound processing hardware and speech recognition software, responds in predictable ways to spoken commands and/or converts speech into text. This tutorial describes the types and the general uses of SR and provides an explanation of the technology behind it. The emerging applications of SR technology for dictation, articulation training, language and literacy development, environmental control, and communication augmentation are discussed.